32 THE QUANTITATIVE VALIDATION OF NONINVASIVE DISEASE ACTIVITY INDICES IN ULCERATIVE COLITIS. (1st March 2006) - Higgins, P. D.R.; Krokos, I.; Leung, J.; Schwartz, M.; Mapili, J.; Zimmermann, E. M.
Abstract : Background and Aims: There are no validated disease activity measures for ulcerative colitis. Current methods of validation are qualitative and provide no means to compare the validity of different indices. Recent data have suggested that two noninvasive indices for ulcerative colitis, the Simple Clinical Colitis Activity Index (SCCAI) and the Seo Index, can predict clinical outcomes of remission and improvement. We performed a quantitative analysis of the psychometric and performance validity of these indices in the measurement of ulcerative colitis. Methods: A longitudinal cohort study of 66 patients with ulcerative colitis was performed at a tertiary care center with repeated measurement of disease activity. Subjects were evaluated with the two noninvasive indices, the St. Mark's Index, and the Inflammatory Bowel Disease Questionnaire. Subjects were also asked at each visit whether they were in remission and at the return visit whether their disease activity had changed. Psychometric validity was evaluated by quantitatively measuring the content, construct, criterion-convergent, and criterion-predictive validity on a 0-1 scale. Performance validity was evaluated by measuring the reproducibility and responsiveness on a 0-1 scale. These items were totaled to provide an overall validity score for each index. Results: The two noninvasive indices had good criterion-convergent and criterion-predictive validity and good reproducibility. The SCCAI was weak in its content validity and in its responsiveness. The Seo Index had weaknesses in its content validity, construct validity, and responsiveness. Both indices had fair overall validity scores, and the SCCAI was superior to the Seo Index. Conclusions: These two noninvasive indices for ulcerative colitis have fair overall validity and are now the most rigorously validated disease activity indices for ulcerative colitis. Both indices predict the clinical end point of patient-defined remission. These noninvasive indices can lower costs and subject discomfort in future clinical trials. Quantitative evaluation of validity identifies weaknesses in disease activity indices that can be improved and can lead to better indices of disease activity in ulcerative colitis and in other disease states.